ماهية برامج الكمبيوتر في ضوء احكام القانونيين العراقي والانكليزي: دراسة تحليلية مقارنة - خلف, علي محمد (Journal of Legal Sciences, 2020)
Computer programs are works of importance of trade, scientific and practical, which is one of the key imports of industrialized countries such as the United States. Historically, computer programs have been found in commercial use since the sixties of the last century where the value is increasing day after day. This shows the urgent need to use them in our personal lives, let alone use in our business. However, it was during our study in the UK, I did not find what refers to determining what computer programs virtually, either through judicial decisions or legally, through legislation, both in common law countries that pursue curriculu Anglo-American system such as the law of England, and the U.S. or countries that pursue the curricu-lum Latin any civil such as the law and the Iraqi French.it was raised several questions in the research whether computer pro grams are thing and if so, are they tangibles or intangibles and what are the circumestances of this. In light of this research, it will focus on highlighting the theoretical and practical (judicial and legislative) to understand the nature of these programs. Researcher raised some questions to analysis of what the computer programs, and therefore, the methodology of this paper relies on the analysis and comparison of the provisions of civil law in Iraq and between the provisions of the common laws in England and the USA…